THE EPISTEMOLOGY OF KHARIQUL’ADAH PHENOMENA IN THE QUR’AN: MIRACLES, KARAMAH, IRHAṢ, AND MAGIC WITHIN A THEMATIC EXEGETICAL FRAMEWORK AND THEIR IMPLICATIONS FOR CONTEMPORARY ISLAMIC EDUCATION - A. Syarofuddin Yusuf Arroziqi; Mu'min Firmansyah (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study examines the epistemology of the khāriq li al-ʿādah phenomenon in the Qurʾān encompassing miracles, karāmah, irhāṣ, and sorcery employing a thematic exegesis (tafsīr maudūʿī) approach. This library research analyzes classical tafsir sources including al-Ṭabarī’s Jāmiʼ al-Bayān, Tafsīr Ibn Kathīr, al-QurṬubī’s al-Jāmiʼ li Aḥkām al-Qurʾān, alongside contemporary academic literature. The study yields three principal conceptual contributions: (1) attributional epistemology, positioning the source rather than the intensity of a phenomenon as the criterion of truth; (2) an epistemological classification of the four phenomena based on their source, purpose, and orientation; and (3) a Qurʾānic Epistemic Literacy model integrating source awareness, critical thinking, moral sensitivity, and orientation toward transcendent truth. The study further formulates pedagogical implications encompassing the integration of revelation-based epistemology into curricula, the cultivation of Qurʾānic-value-grounded critical literacy, and learning models that unite rationality with spirituality. In so doing, it contributes to the development of a more holistic and integrative epistemological framework for Islamic education. Keywords : Khāriq li al-ʿādah, Islamic Epistemology, Thematic Exegesis, Miracle, Islamic Education